Stunting Prevention Movement in the Cibeurem Community Area - Indarna, Asep Aep; Suprapti, Tuti; Anri, Anri; Valani, Cici; Safari, Uum; Lengga, Vivop Marti; Soleha, Sri; Isviyanti, Isviyanti (PT FORMOSA CENDEKIA GLOBAL, 2024)
Stunting is a condition of failure to grow in children under five years old as a result of chronic malnutrition so that the child is too short for his age. Malnutrition occurs from the time the baby is in the womb and in the early days after the baby is born. Stunting in toddlers needs special attention because it can hinder children's physical and mental development. Activities. This community service aims to increase the knowledge, awareness and concern of the people of Cibeureum village about stunting. Method The method in this activity is service learning. The technique of this activity is to start with the distribution of pre-test questionnaires and continue with the provision of materials related to stunting. Furthermore, as an evaluation, a post-test is given. There is an increase in public knowledge about the results of this community service activity show an increase in the knowledge of activity participants about stunting and stunting prevention.